Pregnancy-related Mortality in the United States, 2003-2016: Age, Race, and Place of Death. Issue 1 (24th March 2021) - Burgess, A.P.H.; Dongarwar, D.; Spigel, Z.; Salihu, H.M.; Moaddab, A.; Clark, S.L.; Fox, K.
Abstract : ( Am J Obstet Gynecol . 2020;222:489.e1–489.e8) In the United States, the pregnancy-related mortality rate (PRMR), is several times higher than that of other high-income countries and this has been attributed to a number of medical, social, political, and cultural factors. Programs aimed at addressing this problem have been developed by the Society for Maternal-Fetal Medicine and the American College of Obstetricians and Gynecologists, but there is a lack of data on their impact. This study used data on the place of death, age of death, and deaths by race and ethnicity to explore the contributions of medical factors compared with social, cultural, and environmental factors in pregnancy-related deaths.